Fear of blood, injury, and injections, and its relationship to dental anxiety and probability of avoiding dental treatment among 18-year-olds in Norway - MARGRETHE VIKA, ERIK SKARET, MAGNE RAADAL, LARS-GÖRAN ÖST, & GERD KVALE (IAPD and Blackwell, 2008)
Blood–injury–injection phobia (BIIP) is unique compared to other specific phobias because of a characteristic vaso-vagal response with a strong tendency of fainting when the patient is exposed to the phobic stimuli